2019
DOI: 10.20902/ijptr.2019.120106
|View full text |Cite
|
Sign up to set email alerts
|

Inhibitory Activity Goblet Depletion and focal inflammatory Phaleria macrocarpha Leaves Ethanol Extract on Crypta Mouse after Dextran Sodium Sulphate Induction

Abstract: Colitis Ulcerative is a major public health problem throught the worldwide. Recently many studies have focused to finding antinflammatory based on the natural product. The study was aimed to investigative the inhibitory activity of Phaleria macrocarpa leaves extract on goblet cell in colitis ulcerative. Methods: In this study, Swiss mice were induced by 2% dextran sodium sulfate during a week. Phaleria macrocarpa leaves extract each dose of 100, 200, and 300 mg daily and aspirin 0.2 mg, administered orally. Hi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
5
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 9 publications
(7 reference statements)
0
5
0
Order By: Relevance
“…The dried material then undergo maceration using method adapted from the method of Wilson. 14 The fine dried powder (1000g) was soaked with 3 L 70% ethanol solvent. After 24 hours, the extract was filtered through using Whatman filter paper no.1 to take the filtrate.…”
Section: Plant Extract Preparationmentioning
confidence: 99%
See 2 more Smart Citations
“…The dried material then undergo maceration using method adapted from the method of Wilson. 14 The fine dried powder (1000g) was soaked with 3 L 70% ethanol solvent. After 24 hours, the extract was filtered through using Whatman filter paper no.1 to take the filtrate.…”
Section: Plant Extract Preparationmentioning
confidence: 99%
“…The extract obtained by maceration produced phenol with a grade of 4.4103% or 44.103 GAE/g and flavonoids with levels of 0.3429% or 3.429 mgQE/g, and have IC 50 219.716 μg/mL (moderate antioxidant intensity). 14…”
Section: Plant Extract Preparationmentioning
confidence: 99%
See 1 more Smart Citation
“…Uncontrolled activation of neutrophils with UC causes damage to the colonic epithelial tissue and allows infiltration into the crypts [21]. Showed the antiinflammatory effect of P. macrocarpa leaf extract by suppressing the amount of inflammatory focus in DSS-induced UC [16].…”
Section: Discussionmentioning
confidence: 99%
“…From this study, it was concluded that the P. macrocarpa leaf extract can reduce colonic tissue damage and prevent an increase in the expression of COX-2, NOS and β-catenin [15]. A study by Maharani et al showed that the P. macrocarpa leaf extract with a dose of 100 mg, 200 mg, and 300 mg can inhibit a decrease in the number of goblet cells in the colon [16].…”
Section: Effect Of Administration Of P Macrocarpa Leaf Extract On the Number Of Goblet Cellsmentioning
confidence: 99%